Hypoxia-induced factor-1 alpha (HIF-1a) mRNA expression in human muscles and leucocytes - Mounier, R.; Roels, B.; Pialoux, V.; Thomas, C.; Mercier, J.; Millet, G.; Coudert, J.; Clottes, E.; Fellmann, N. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
HIF-1 is a transcriptional factor playing a key role in cellular responses to low oxygen tension (Semenza, 1998). This heterodimeric protein is made up of two subunits named HIF-1Alpha and HIF-1Beta. The beta protein is constitutively expressed whereas the HIF-1Alpha protein expression is tightly linked to a decreased oxygen level. In cells exposed to hypoxia, HIF-1 up-regulates the transcription of various genes responsible for the adaptation to hypoxia. HIF-1Alpha gene expression in human muscle needs invasive muscle biopsies. Human leukocytes and muscle express HIF-1Alpha gene. Therefore, the aim of our study was double: we first wanted to study HIF-1Alpha mRNA amount variations in muscles of athletes subjected to a hypoxic training program. Secondly, we wanted to determine if in these subjects, HIF-1Alpha mRNA amount variations were comparable in both leukocytes and muscle. Methods Ten well-trained endurance athletes completed a three week hypoxic training program, consisting of two interval-training sessions at 90 to 100% of VO2max and three steady work sessions at 60% of VO2max per week. All training sessions were performed under hypoxic conditions (simulated altitude of 3,000 m, PIO2 . 100 mmHg, Altitrainer 200.). Blood samples and muscle biopsies were taken at rest from vastus lateralis before and after the training period. The biopsies were performed using the technique of Bergstrom with suction. Muscle and leukocyte total RNA were extracted and reverse-transcribed. HIF-1Alpha mRNA levels were determined using real time PCR. The values were normalised using the expression of Beta2 microglobulin as a house-keeping gene. Results HIF-1Alpha mRNA basal values varied in a large extend between subjects in leukocytes and muscle. A large inter-subject variability of the response to hypoxic training program regardless the tissue was also observed (-705% to +92% for leukocytes, -141% to +50% for muscle) (Fig.1). In average, a significant HIF-1Alpha. mRNA amount decrease was only observed in muscle after the hypoxic training program (p = 0.01) (Fig.2). There was no significant correlation between the variation of HIF-1Alpha mRNA amounts (%) during the hypoxic training program in muscle and leukocytes. Discussion/Conclusion These results show that: 1) a large inter-subject variability of HIF-1Alpha mRNA expression is present in muscle and leukocytes; 2) the hypoxic training program significantly lowers HIF-1Alpha mRNA amounts in muscle but not in leukocytes even though a slight tendency to a decrease is observed. Therefore, considering small sample the actual leukocytes variations do not allow to be used as relevant index of muscle changes.